Upon All Flesh: An Ecological Reading of Acts 2.17–21 - Griffiths, John D. (Journal for the study of the New Testament, 2025)
The Lukan Peter’s quotation of LXX Joel 3.1–5a is the central co-text that frames the outpouring of the Spirit in Acts 2. In this article, I offer three supporting arguments for understanding πᾶσα σάρξ found in Acts 2.17 as referencing all of creation. First, the connection between the Spirit of God and all flesh in the Hebrew Bible always has a creation-wide context. This connection between Spirit and flesh then introduces the flood narrative as a key co-text for Joel 2.28, as Joel sees the outpouring of the Spirit as an inversion of the withdrawal of the Spirit at the flood. Third, this creation-wide understanding of πᾶσα σάρξ in Acts 2.17 is further supported by three editorial changes the Lukan Peter makes to his quotation of LXX Joel 3.1–5a. Therefore, the outpouring of the Spirit at Pentecost is a creation-wide event.